ENVIRONMENTAL PROBLEMS OF WASTE DISPOSAL AT THE PRESENT STAGE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
One of the most important aspects of ensuring the safety and health of the population is the creation of normal conditions for living and living. Taking this factor into account, this article examines environmental problems associated with waste disposal at the present stage. By the end of the twentieth century, humanity faced acute problems of waste disposal in all regions and countries of the world as one of the negative factors of the world community. In this regard, great interest was noted by states in the issues of eliminating the large-scale increase in all kinds of waste. The article also analyzes the negative consequences of the waste disposal process and gives recommendations for eliminating deficiencies.